2017
DOI: 10.1097/id.0000000000000622
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Abutment Surface Treatments on Screw Loosening of Morse Taper Implants

Abstract: The association of blasting and bonding on abutment surface can be used to prevent screw loosening in Morse taper implants.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 33 publications
0
1
0
Order By: Relevance
“…However, it has been demonstrated that extraoral cementation significantly decreases the amount of cement excess [ 4 ]. Many surface treatments, such as sandblasting, silicatization, plasma spraying, primer application, and laser etching [ 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 ], have been suggested to achieve higher bond strength between resin cement and dental ceramics for dental-supported restorations. Sandblasting metal oxide-based substrates with aluminum oxide particles (Al 2 O 3 ) or silica-coated particles demands specific equipment.…”
Section: Introductionmentioning
confidence: 99%
“…However, it has been demonstrated that extraoral cementation significantly decreases the amount of cement excess [ 4 ]. Many surface treatments, such as sandblasting, silicatization, plasma spraying, primer application, and laser etching [ 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 ], have been suggested to achieve higher bond strength between resin cement and dental ceramics for dental-supported restorations. Sandblasting metal oxide-based substrates with aluminum oxide particles (Al 2 O 3 ) or silica-coated particles demands specific equipment.…”
Section: Introductionmentioning
confidence: 99%